Report letter from Irkutsk official S. A. Shimansky with recommendation to deport Jews from Russia to the Supreme Ruler Admiral A. V. Kolchak (December 1918) - A. V. Sushko; M. M. Stelmak (Омский научный вестник: Серия "Общество. История. Современность")
This archaeographic publication is devoted to the study of the Jewish question during the Civil War in the east of Russia. A memorandum of the Irkutsk official S. A. Shimansky to the Supreme Ruler Admiral A. V. Kolchak with a proposal to deport Jews from Russia is added. The introductory preface to the document, based both on the works of historians on the situation of Jews in Russia and on clerical sources characterizing the personality of the author of the memo, analyzes the conditions that made it possible for an official in White Siberia to create it. The publication is of interest to researchers of the events of the Russian Revolution and the Civil War in Russia, the ethnopolitical history of the Russian state and Siberia.